80-kVp CT angiography for endovascular aneurysm repair follow-up with halved contrast medium dose and preserved diagnostic quality. (March 2016) - Lehti, Leena; Nyman, Ulf; Söderberg, Marcus; Björses, Katarina; Gottsäter, Anders; Wassélius, Johan
Background: Follow-up of endovascular aneurysm repair (EVAR) with life-long computed tomography angiography (CTA) surveillance exposes patients with impaired renal function to repeated risks of contrast medium-induced nephropathy (CIN). Purpose: To retrospectively compare vascular attenuation, image noise, contrast-to-noise ratio (CNR), subjective image quality and effective radiation dose (mSv) for CTA with a 16-multirow detector CT (MDCT) equipment at 80 kVp after EVAR using a contrast medium (CM) dose that is half of that used at 120 kVp. Material and Methods: Forty patients with estimated glomerular filtration rate (eGFR) <45 mL/min underwent 80-kVp CTA with 160 mg I/kg, and 40 patients with eGFR ≥45 mL/min 120-kVp CTA with 320 mg I/kg (maximum dose weight, 80 kg). Arterial phase analysis included vascular attenuation, image noise and CNR, and calculated effective dose. Subjective image quality was assessed on a 4-point scale by two blinded readers at three different levels as well as overall. Results: Median values in the 80/120 kVp cohorts were: age, 74–75 years; body weight, 77/80 kg; BMI 24/27 kg/m 2 ; CM dose, 13/25 gram-iodine; gram-iodine/GFR ratio, 0.35/0.38; mean aortic attenuation, 313/326 HU; image noise, 26/32 HU; CNR 10–11; subjective image quality score, 3.0–3.5 (Reader 1) and 3.0–3.3 (Reader 2); number of non-diagnostic examinations, 0/1; and effective dose, 4.5/5.1 mSv. There was no statistically significant difference in aortic CNR and effective dose between the 80 and 120 kVp cohorts. Conclusion: 80 kVp 16-MDCT with halved CM dose tailored to body weight for CTA follow-up of EVAR may provide satisfactory diagnostic results compared to common standards and be beneficial for patients at risk of CIN, though the present CT equipment may limit the use of the method to patients below 90 kg or with a BMI below 35 kg/m 2 .